Development and validation of reversed phase high performance liquid chromatographic method for determination of amlodipine - Alaama, Mohamed; Helal Uddin, A.B.M.; Mohamad, Huda Jamilah; Amiruddin, Noor Syafawati; SA, Abbas (Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, 2015)
Purpose: To develop and validate a new sensitive and low-cost method for the analysis of amlodipine in tablet dosage form using reversed phase high performance liquid chromatography (RP-HPLC) with ultraviolet (UV) detection. Methods: Standards and samples were prepared by dissolving amlodipine besylate standard or amlodipine tablets in mobile phase and sonicated for 5 min. The samples were analysed by RP-HPLC equipped with quaternary pump and auto-injector. Separation was achieved using C18 column, and the mobile phase consisted of ammonium acetate buffer containing 0.02 % triethylamine TEA (pH = 4, adjusted using glacial acetic acid) and acetonitrile in the ratio 60:40 v/v. The flow rate was 1 ml/min and a UV detector was used for the detection of amlodipine at a wavelength of 248 nm. The method was validated according to International Conference of Harmonization (ICH) guidelines. Results: The retention time for amlodipine peak was 3.44 ± 0.41 min with a total run time of 6 min. The method was linear over the range of 0.5 - 40 μg/ml with coefficient of determination (R2) of 0.999. Recovery was 98.09 - 100.19 %, and the method showed high precision and repeatability. All validated parameters were within the range of ICH requirements. Conclusion: A new rapid sensitive and low-cost method has been developed and validated for the analysis of amlodipine in tablet dosage form.